Historical Analysis of World War II and its Implications for the Readiness of the RSPAD Medical Laboratory - Prabowo, Endra Tri; Uksan, Arifuddin; Subiantoro, Yudi (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2026)
World War II marked a critical turning point in the development of military medical laboratories, transforming them from purely clinical support units into strategic elements of national defense systems. Operational pressures on the battlefield, high rates of infectious diseases, and the threat of biological weapons stimulated innovations such as field laboratories, rapid diagnostic methods, mass production of antibiotics, and military sanitation protocols. These historical lessons remain highly relevant in addressing contemporary health threats, making it essential to examine their implications for the readiness of the Medical Laboratory of RSPAD Gatot Soebroto as the primary military hospital of the Indonesian Army. This study aims to analyze the development of military medical laboratories during World War II and its implications for the readiness of laboratory infrastructure, medical human resources, and operational protocols at RSPAD. This research employs a descriptive qualitative approach, with data collected through interviews, analysis of official documents, academic literature review, and observation, and examined using data triangulation. The analytical framework is based on the Military Health System, particularly the Clinical Readiness Program (CRP) and Knowledge, Skills, and Abilities (KSA), supported by perspectives from defense studies and Historical Institutionalism. The findings indicate that World War II functioned as a critical juncture that shaped patterns of military medical laboratory readiness, subsequently adopted by RSPAD through strengthened laboratory infrastructure, enhanced medical personnel readiness, and the implementation of biosurveillance and outbreak response protocols. The study concludes that effective medical laboratory readiness can only be achieved through the integrated development of infrastructure, human resources, and operational protocols. It is recommended that RSPAD strengthen the sustained implementation of CRP and KSA while further developing mobile laboratory capabilities and expanding health defense cooperation.